2021
DOI: 10.1021/acsomega.1c01744
|View full text |Cite
|
Sign up to set email alerts
|

Why Should Metformin Not Be Given in Advanced Kidney Disease? Potential Leads from Computer Simulations

Abstract: Metformin is considered as the go-to drug in the treatment of diabetes. However, it is either prescribed in lower doses or not prescribed at all to patients with kidney problems. To find a potential explanation for this practice, we employed atomistic-level computer simulations to simulate the transport of metformin through multidrug and toxin extrusion 1 (MATE1), a protein known to play a key role in the expulsion of metformin into urine. Herein, we examine the hydrogen bonding between MATE1 and one or more m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…This binding geometry may represent the first step in the recognition of MATE1 by PAs after entering the central cleft produced by the C- and N-lobes (see SI for additional views of the docked PAs). Functional analysis of hMATE1 mutants by site-directed mutagenesis in conjunction with transport assays have demonstrated that highly conserved Glu-273, Glu-278, Glu-300, and Glu-389 are critical for substrate translocation. , Homology models inspired by eukaryotic MATE1 strongly suggest that the C-lobe with its conserved acidic amino acid residues (Glu-273, Glu-389) and H-bonding network does not only mediate proton antiport but also harbors residues critical for transport efficiency and substrate selectivity. , Finally, recent docking and molecular dynamics simulations on the MATE1-mediated extrusion of the antidiabetic drug metformin show intermolecular interactions with Glu-273, Trp-274, Tyr-277, and Glu-389, which are also observed for the docked PAs. Thus, the ligand geometries observed for the PAs are consistent with the previously proposed mechanism of hMATE1-mediated substrate transport.…”
mentioning
confidence: 99%
“…This binding geometry may represent the first step in the recognition of MATE1 by PAs after entering the central cleft produced by the C- and N-lobes (see SI for additional views of the docked PAs). Functional analysis of hMATE1 mutants by site-directed mutagenesis in conjunction with transport assays have demonstrated that highly conserved Glu-273, Glu-278, Glu-300, and Glu-389 are critical for substrate translocation. , Homology models inspired by eukaryotic MATE1 strongly suggest that the C-lobe with its conserved acidic amino acid residues (Glu-273, Glu-389) and H-bonding network does not only mediate proton antiport but also harbors residues critical for transport efficiency and substrate selectivity. , Finally, recent docking and molecular dynamics simulations on the MATE1-mediated extrusion of the antidiabetic drug metformin show intermolecular interactions with Glu-273, Trp-274, Tyr-277, and Glu-389, which are also observed for the docked PAs. Thus, the ligand geometries observed for the PAs are consistent with the previously proposed mechanism of hMATE1-mediated substrate transport.…”
mentioning
confidence: 99%